Pengaruh Rasio Keuangan Terhadap Harga Saham dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Tambang Batu Bara di Bursa Efek Indonesia - Irvan Romadhon; Yuniningsih Yuniningsih (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
This research aims to examine the effect of financial ratios on stock prices with profitability as a moderating variable. Financial ratios are arranged from variables of liquidity, solvency, and market value. Coal mining companies being listed on the Indonesia stock exchange are the population in this research. The selection of samples is using a purposive sampling method, therefore it is acquired with 11 companies. Data was collected by combining time-series data and cross-section data. Afterward, these data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) using SPSS software. This research proves that if partially liquidity as measured by Cash Ratio (CR) and market value as measured by Price Earnings Ratio (PER) have a positive effect on stock prices, while solvency as measured by Debt to Equity Ratio (DER) has a negative effect on stock prices. MRA proves if profitability as measured by Earnings Per Share (EPS) as a moderating variable was able to moderate the effect of CR, DER, and PER on stock prices